HUBUNGAN ANTARA PANTENSI FORAMEN OVALE DENGAN KEJADIAN DECOMPRESSION SICKNESS - Ananda Rizkia; Donna Diva Widyantari; Nabila Indah Shofiyanti; Ni Pt Wr Pradnya Nirmala Putri; Arfi Syamsun (Kelompok Ilmiah Hippocrates Fakultas Kedokteran Universitas Udayana, 2023)
Background: Decompression sickness (DCS) is a condition where bubbles form in the blood from dissolved gasses (usually nitrogen) which cause tissue and blood vessel injury due to a decrease in environmental pressure. One of the factors that can increase the incidence of DCS is the presence of patent foramen ovale (PFO) in divers. Method: This literature review is a study systematic review, the type used is the original article obtained through the database PubMed and ProQuest. We use the keywords